Fostering Spatial Efficiency in the Marine Space, in a Socially Sustainable Way: Lessons Learnt From a Soft Multi-Use Assessment in the Mediterranean - Kyvelou, Stella Sofia I.; Ierapetritis, Dimitrios G. (Frontiers in Marine Science, 2021)
In a context of growing claim for marine space and in the pursuit of maritime “spatial efficiency”, Multi-use (MU) becomes necessary to assemble more or less compatible sea uses. In this paper, the potential of the soft MU involving small-scale fisheries (SSF), tourism and nature conservation (related to MPAs), widely encountered in the Mediterranean sea-basin, is being assessed in Greece. Despite the fact that the MU concept is not yet included neither in MSP laws nor in strategic policy documents due mainly to the dominance of terrestrial spatial plans that favour exclusive rights of highly competitive and expansive maritime activities (e.g aquaculture), the above MU is increasingly being practiced by local communities as a socioeconomic instrument (fishing tourism), able to be also occasionally oriented to nature conservation. Following the DABI analysis, a spectrum of challenges/constraints and opportunities for the application of the MU under study were revealed, grouped in socio-economic, environmental, political-regulatory and technological factors that can enable or undermin this MU in the Greek seas. The paper concludes that there is a huge potential for the said MU development in areas dependent on fisheries, consistently to the longstanding SSF tradition that despite its decline, continues to be one of the most important among those practiced in the coastal zone and in remote and insular communities, essentially defining their particular social and cultural identity. Besides, SSF have low environmental impact and also tourists and the local communities are gradually becoming more conservation-oriented. Hence, the MU is highlighted as a tool for sustainable use of marine space supporting the Blue Growth Agenda and reconnecting natural and cultural capital at sea, thus redefining also the role of fishers that under equitable conditions may become defenders of marine biodiversity and key actors for the sustainable management of fish stocks and ecosystems in the protected areas.